KONSEP PENDIDIKAN DALAM AL-QUR'AN - M. Syadli (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2001)
In the world of general education, there have been three kinds of educational theories: the first is tabularasa theory that had been emerged by John Locke (1632-1704) and, later, known as Empirism; the second is talent theory that had been pioneered by Arthur Schopenhour (1768-1860) and, later welllknown as Nativism; and the third is realism theory that had been presented by William Stern (1871-1939) and, later, famous as Convergence.The said three general educational theories above are based on the anthropocentric philosophy, while the Islamic educational theory is based on the theocentric philosophy that is referred to the Holy Qur'an and the Prophet's Traditions. Here below the writer presents and focuses on the Islamic aspects of education which are based on the Holy Qur'an and the Prophet's Traditions. They consist of teacher as a social agent, student, teaching material, method of teaching, goal of teaching that has to be reached, evaluation, educational envirenment and infrastructure.Key word: Anthropocentric, Theocentric, Aspects of Education, The Holy Qur'an